Answer:
(x, y) = (1, 1/3)
Explanation:
The x-coefficient in the first equation is -2 times that in the second equation, so adding twice the second equation to the first will eliminate x:
(4x -9y) +2(-2x +3y) = (1) +2(-1)
-3y = -1 . . . . simplify
y = 1/3 . . . . . divide by -3
The y-coefficient in the first equation is -3 times the y-coefficient in the second equation, so adding 3 times the second equation to the first will eliminate y:
(4x -9y) +3(-2x +3y) = (1) +3(-1)
-2x = -2 . . . . . . simplify
x = 1 . . . . . . . . . divide by -3
The solution is (x, y) = (1, 1/3).